2004
DOI: 10.1136/ip.2004.005181
|View full text |Cite
|
Sign up to set email alerts
|

Using narrative text and coded data to develop hazard scenarios for occupational injury interventions

Abstract: Objective: To determine whether narrative text in safety reports contains sufficient information regarding contributing factors and precipitating mechanisms to prioritize occupational back injury prevention strategies. Design, setting, subjects, and main outcome measures: Nine essential data elements were identified in narratives and coded sections of safety reports for each of 94 cases of back injuries to United States Army truck drivers reported to the United States Army Safety Center between 1987 and 1997. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 14 publications
1
49
0
Order By: Relevance
“…[24][25][26] Narrative text coding based on the Haddon matrix and the hazard scenario frameworks has been shown to provide a comprehensive analysis of the factors contributing to injuries in specific worker populations [27][28][29][30] suggested that the use of narrative analysis of reports based on Haddon's matrix provided more comprehensive information on the human, organizational, and environmental factors con-tributing to worker injuries. FACE fatality investigation reports consist of an examination of the geographic location of the fatality, as well as interviews of witnesses, family, employers, coroners, and others.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26] Narrative text coding based on the Haddon matrix and the hazard scenario frameworks has been shown to provide a comprehensive analysis of the factors contributing to injuries in specific worker populations [27][28][29][30] suggested that the use of narrative analysis of reports based on Haddon's matrix provided more comprehensive information on the human, organizational, and environmental factors con-tributing to worker injuries. FACE fatality investigation reports consist of an examination of the geographic location of the fatality, as well as interviews of witnesses, family, employers, coroners, and others.…”
Section: Resultsmentioning
confidence: 99%
“…As a starting point, the nine ''key data elements'' used by Lincoln et al [2004] in their template for reconstructing injury events were adapted to fit the needs of this study. Other important circumstances of the injuries were captured with additional variables.…”
Section: Narrative Text Codingmentioning
confidence: 99%
“…Our approach was similar to and patterned on an earlier report of narratives used to characterize injuries of U.S. Army truck drivers (Lincoln et al, 2004). Two investigators independently assigned each of the 221 reports to the ten injury scenarios (99.10% initial agreement; all discrepancies were easily resolved).…”
Section: Methodsmentioning
confidence: 99%